Production of elemental sulfur from surface ores - Basiao, Samuel S. (College of Engineering, 1969)
Capacity: 300,000 lbs/day -- Total fixed capital investment: 6,679,500 -- Total product cost at maximum production: 3,740,400 -- Annual sales at maximum production: 5,900,000 -- Pay-out time: 2.36 yrs. -- Maximum annual rate of production: 45,000 tons -- Break-even point: 14% of maximum capacity -- Percent return on fixed capital investment before taxes: 32.4%